2020
DOI: 10.1016/j.heliyon.2020.e04205
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides from bacteria and fungi: current status and perspectives in Africa

Abstract: Bacterial and fungal exopolysaccharides (EPSs) are extracellular metabolites of living organisms (plants, animals, algae, bacteria and fungi) associated with adaptation, survival and functionalities. The EPSs also afford humans multiple value-adding applications across different spheres of endeavors. The variable chemical and biochemical architecture that characterizes an EPS presets its biological functionality and potential biotechnological benefits. Suffices to say that it is amenable to genetic, biotechnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 80 publications
(123 reference statements)
0
30
0
1
Order By: Relevance
“…Administration of nasal formulations [4] Sphingomonas paucimobilis Tissue engineering and bone regeneration [25] n.a. Injectable gellan-based hydrogel to treat a bone defect [38,39] Nano-hydrogel for drug delivery [19] Composite scaffold for skin regeneration [27] Lactic acid bacteria Microencapsulation matrix for drug delivery [12] Levan Halomonas smyrnensis Levan-based scaffold for tissue engineering [40] Multilayer film for the enhancement of live cell adhesive properties, harbor aldehyde groups for antitumor properties [41] Disintegration agent in immediate-release tablets [16] Sulfated levan for cardiac tissue engineering [42] Bacillus subtilis, Streptococcus mutans, Streptococcus salivarius…”
Section: Paenibacillus Polymyxamentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of nasal formulations [4] Sphingomonas paucimobilis Tissue engineering and bone regeneration [25] n.a. Injectable gellan-based hydrogel to treat a bone defect [38,39] Nano-hydrogel for drug delivery [19] Composite scaffold for skin regeneration [27] Lactic acid bacteria Microencapsulation matrix for drug delivery [12] Levan Halomonas smyrnensis Levan-based scaffold for tissue engineering [40] Multilayer film for the enhancement of live cell adhesive properties, harbor aldehyde groups for antitumor properties [41] Disintegration agent in immediate-release tablets [16] Sulfated levan for cardiac tissue engineering [42] Bacillus subtilis, Streptococcus mutans, Streptococcus salivarius…”
Section: Paenibacillus Polymyxamentioning
confidence: 99%
“…The classification of bacterial EPSs is shown in Figure 2. Exopolysaccharides produced by bacteria can promote intestinal health, altering microbes' composition, enhancing immune activity, and improving blood flow [4,11,12]. Cellulose, dextran, xanthan gum, HA, ALG, kefiran, gellan, levan, and curdlan are some of the microbial EPSs with biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) revealed that, species of genus Pleurotus capable of utilizing different agrowastes to produce polysaccharides. Fungal polysaccharides, especially EPS possess therapeutic properties like antimicrobial, antioxidant, and anticancer ( Osemwegie et al., 2020 ). This has made EPS to receive greater interest for extensive applications in food, pharmaceutical, and cosmeceutical industries ( Ozcan and Oner, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A classificação dessas macromoléculas se dá conforme sua localização no organismo produtor, em polissacarídeos citosólicos (fontes de carbono e energia para a célula), polissacarídeos de parede celular, ligados ou não a proteínas, e polissacarídeos secretados para o meio extracelular, formando cápsulas ou biofilme, denominados exopolissacarídeos (EPS). Em destaque, os exopolissacarídeos produzidos por bactérias e fungos têm sido amplamente aplicados nas indústrias de alimentos, medicamentos, cosméticos, entre outras (Osemwegie, 2020).…”
Section: Introductionunclassified